Consequence Study of CO2 Droplet Leakage in Seawater using Computational Fluid Dynamic (CFD) Approach - Mohd Zaini, Mohammad Haniff (IRC, 2016)
Broaden of human knowledge in technology had rapidly development the industrial sector worldwide. However, it is still far away for us to have the technology which would be sustainable to the earth environment. This had caught the attention of the people worldwide about the need to have a more sustaining system in industry that had less effect to the earth. Known as one of the oldest negative contribution to sustainability is the release of carbon dioxide into the atmosphere. Most of the carbon dioxide came from industries that involve the production of carbon dioxide namely a power plant. Release of carbon dioxide causes the earth to warm up. This is called global warming. It potentially could bring harm to the living creature as it would affect the chain of life in the system